DEVELOPING BOOKLET BASED ON THE RESEARCH RESULT OF THE EFFECT OF FORMALIN-ADDED-TOFU TO HEPAR HISTOPATOLOGY OF MALE MICE Balb/C STRAIN - Egi Qory Imamah; Umi Lestari; Abdul Gofur (JPBI (Jurnal Pendidikan Biologi Indonesia), 2016)
Formalin is a dangerous food preservative which has been banned to be used. Formalin is often used because it is relatively cheap and simple to use. This study aimed to analyze the effect of formalin to damage liver histology of male mice. Mice used were male mice Balb/C strain aged 4 weeks and weighted 20 to 22 grams. The extract of formalin-added-tofu, which were the concentration of: 0.1%, 1.68%, and 3.35%, 5.1%, 6.7%, were given orally per day for 12 weeks. At the end of 12th week, the mice were dissected and the liver were taken which then made preparations. The liver histological preparations were observed under a dino lite microscope in five different visual field, with a magnification of 800 times. For each of field of views, 20 cells were randomly counted. The average of weighted score of histopathological liver of five field of views then were randomly calculated for each mice. The scoring model used was Histopathology Manja Roenigk. The total of damage percentage occurred was recorded and calculated. The results showed that oral exposure to formaldehyde increases the amount of damage significantly in male mice strain Balb/C. The research results were presented in the form of booklets as a means of communication to the public media to broaden the danger of formalin-added-tofu. The booklet was made in order to perform the role of education as an agent of society renewal insight and knowledge. In addition, it also creating a continuous learning.Keywords: Booklet, Formalin, Hepar Histology, Male Mice, Tofu